2022
DOI: 10.1186/s12876-022-02269-y
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder-preserving polypectomy for gallbladder polyp by embryonic-natural orifice transumbilical endoscopic surgery with a gastric endoscopy

Abstract: Background and aims Cholecystectomy is performed for most gallbladder polyps (GPs). However, cholecystectomy results concerning complications in some patients. For benign GPs, adoption of gallbladder-preserving surgery is worth to recommend. We describe our experiences performing gallbladder-preserving polypectomy for GPs by embryonic-natural orifice transumbilical endoscopic surgery (E-NOTES) with a gastric endoscopy. Methods This is a retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…To assess the treatment effect of gallbladder-preserving therapy, the methods of testing the gallbladder function have to be mentioned. Currently, gallbladder-emptying function is assessed clinically by comparing the variation of cholecyst volume between fasting and high-fat diet with the help of ultrasound [ 27 , 38 , 41 ]. This approach approximately treats the irregularly shaped gallbladder as a regular ellipsoid [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To assess the treatment effect of gallbladder-preserving therapy, the methods of testing the gallbladder function have to be mentioned. Currently, gallbladder-emptying function is assessed clinically by comparing the variation of cholecyst volume between fasting and high-fat diet with the help of ultrasound [ 27 , 38 , 41 ]. This approach approximately treats the irregularly shaped gallbladder as a regular ellipsoid [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they should evaluate the feasibility of gallbladder preservation according to what they see intraoperatively. It has been demonstrated that gallbladder emptying functions return to preoperative levels 1 year after surgery and devices to close the gallbladder wound (such as hemostatic clips) do not provoke discomforts in patients or affect gallbladder functions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies on pure NOTES have proposed procedures as attractive alternative options for intra-abdominal procedures. [18][19][20] However, some technical obstacles remained including the risk of fecal contamination and peritoneal infection, availability of methods for safe entrance into the peritoneal cavity as well as for reliable entry site closure. [21,22] A recent study confirmed the efficacy of using a detachable endo-colonic balloon to keep the distal colonic and rectal lumen clean and aseptic during transrectal NOTES endoscopic procedures.…”
Section: Technical Obstacles In Notes Adoptionmentioning
confidence: 99%